Improved dynamic performance of permanent magnet synchronous generator based grid connected wind energy system - Rani, Preeti; Arora, Ved Parkash; Sharma, Naveen Kumar (Energy sources. Part A, Recovery, utilization, and environmental effects, 2022)
This comprehensive work investigates the reactive power control capability of a dynamic voltage restorer (DVR) for a permanent magnet synchronous generator (PMSG)-based grid-connected wind energy system (WES). Series compensation scheme-based DVR is employed to mitigate three-phase faults by injecting regulated voltage at the point of common coupling (PCC) bus through a series injection transformer. An improved hysteresis controller, a multi-loop-based controller consists of a hybrid system of the conventional PI controller, and feed-forward with feedback loop-based voltage-controlled DVR is the novelty of this article. DVR-modified hysteresis control highlights how grid-connected WES might increase their stability and dynamic performance. The suggested approach operates quickly, smoothly, and consistently, and it is designed and implemented in Matlab-Simulink software, and the performance of the proposed controller is validated with a comparative analysis between conventional synchronous reference frame controller DVRs. As a result, the total performance can demonstrate the efficiency of the recommended strategy. The suggested system produces very low THD values, 1.04% for grid-connected WES, when compared to the other approach. The instructive subject of this work, the clear choice of control method and electric circuit, ensures that the optimal fact of DVR topology meets the required power quality. This study also provides useful information to researchers in this sector.